GROWTH OF Manilkara huberi AND Manilkara paraensis AFTER LOGGING AND SILVICULTURAL TREATMENTS IN THE MUNICIPALITY OF PARAGOMINAS, PARÁ, BRAZIL - Souza, Deivison Venicio; Carvalho, João Olegário Pereira de; Mendes, Fernanda da Silva; Melo, Lia de Oliveira; Silva, José Natalino Macedo; Jardim, Fernando Cristóvam da Silva (Floresta, 2014)
Abstract The effects of silvicultural treatments and logging on the growth rates of Manilkara huberi and Manilkara paraensis in a terra firme natural forest were evaluated. The study was performed in a Forest Management Unit (FMU) located in the municipality of Paragominas, PA. The experimental area covered 500 ha, where five treatments (100 ha each), with four replications per treatment (25 ha each), were established. The replications were randomly distributed in the 500 ha sample area of the FMU. The growth rate of trees was evaluated in the following treatments: T1 – Reduced Impact Logging (RIL) + classic liberation thinning and climber cutting; T2 – RIL + modified liberation thinning and climber cutting; T3 – RIL + climber cutting; T6 - only RIL; T7 - unlogged forest (control). Manilkara huberi and Manilkara paraensis showed good responses on diameter growth rate to the post-harvesting silvicultural treatments applied. However, considering the growth rate differences between the evaluated periods, one can say that the short time elapsed from the application of silvicultural treatments (four years) to the end of the study period does not allow to make accurate statements about the most appropriate treatment for the species, or about the intensity of the interventions to be applied. Keywords: Diameter increment; post-harvesting silviculture; tree girdling; climber cutting. Resumo Crescimento de Manilkara huberi e Manilkara paraensis após a colheita de madeira e tratamentos silviculturais, paragominas, Pará, Brasil. Foram avaliados os efeitos de tratamentos silviculturais e da colheita de madeira sobre o crescimento diamétrico das espécies Manilkara huberi e Manilkara paraensis em uma floresta natural de terra firme. A pesquisa foi conduzida em uma Unidade de Manejo Florestal (UMF), município de Paragominas, PA. A área experimental correspondeu a 500 ha, onde foram estabelecidos cinco tratamentos (100 ha cada) com quatro repetições (25 ha cada). As repetições foram distribuídas aleatoriamente na amostra de 500 ha na UMF. O crescimento das árvores foi avaliado nos seguintes tratamentos: T1 – exploração de impacto reduzido (EIR) + desbaste de liberação clássico e corte de cipós; T2 – EIR + desbaste de liberação modificado e corte de cipós; T3 – EIR + corte de cipós; T6 – apenas EIR; T7 - floresta não-explorada. Manilkara huberi e Manilkara paraensis mostraram respostas favoráveis, em termos de crescimento em diâmetro, às intervenções silviculturais pós-exploratórias aplicadas. Contudo, considerando as diferenças no incremento das árvores entre os períodos avaliados, pode-se dizer que o curto espaço de tempo decorrido da aplicação dos tratamentos silviculturais (quatro anos) ainda não permite fazer projeções precisas acerca do tratamento mais adequado às espécies, ou mesmo, da intensidade das intervenções a serem aplicadas. Palavras-chave: Incremento diamétrico; silvicultura pós-colheita; anelagem de árvores, corte de cipós.